An experimental-numerical method for the calibration of finite element models of the lumbar spine. (September 2022) - Nicolini, Luis Fernando; Beckmann, Agnes; Laubach, Markus; Hildebrand, Frank; Kobbe, Philipp; Mello Roesler, Carlos Rodrigo de; Fancello, Eduardo Alberto; Markert, Bernd; Stoffel, Marcus
Highlights: An automated stepwise method calibrates computational models of the spine. A Genetic Algorithm optimizes 11 material parameters of the intervertebral disc. The mechanical property of the ligament is determined with only one simulation. The Finite Element model reproduces the experimental results after calibration. The algorithms, protocols and tutorials are open source. Abstract: We present a systematic and automated stepwise method to calibrate computational models of the spine. For that purpose, a sequential resection study on one lumbar specimen (L2-L5) was performed to obtain the individual contribution of the IVD, the facet joints and the ligaments to the kinematics of the spine. The experimental data was prepared for the calibration procedure in such manner that the FE model could reproduce the average motion of the 10 native spines from former cadaveric studies as well as replicate the proportional change in ROM after removal of a spinal structure obtained in this resection study. A Genetic Algorithm was developed to calibrate the properties of the intervertebral discs and facet joints. The calibration of each ligament was performed by a simple and novel technique that requires only one simulation to obtain its mechanical property. After calibration, the model was capable of reproducing the experimental results in all loading directions and resections.